2015
DOI: 10.1542/peds.2015-1068
|View full text |Cite
|
Sign up to set email alerts
|

Family Experience and PICU Death: A Meta-Synthesis

Abstract: BACKGROUND AND OBJECTIVES: The PICU is the most common site for inpatient pediatric deaths worldwide. The impact of this clinical context on family experiences of their child's death is unclear. The objective of the study was to review and synthesize the best available evidence exploring the family experience of the death of their child in the PICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 39 publications
(37 reference statements)
3
16
0
1
Order By: Relevance
“…This is in line with findings that grieving parents need significant others, helpers, and witnesses to what happened (19,25,26). Medical and nursing staff can fulfill this role when the mourning process starts when the child is still in the PICU (9,23). In line with the conclusion of the study of Sand and Strang (14) on existential loneliness, our study confirms that feelings of loneliness may decrease through empathic human encounters with care providers and experiences of mutual togetherness.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is in line with findings that grieving parents need significant others, helpers, and witnesses to what happened (19,25,26). Medical and nursing staff can fulfill this role when the mourning process starts when the child is still in the PICU (9,23). In line with the conclusion of the study of Sand and Strang (14) on existential loneliness, our study confirms that feelings of loneliness may decrease through empathic human encounters with care providers and experiences of mutual togetherness.…”
Section: Discussionsupporting
confidence: 85%
“…Second, the professionality of medical staff as seen in their actions and behavior is another way of showing connection. Doctors trying their utmost or doing unconventional things communicate to parents that both their child and they themselves matter (23).…”
Section: Discussionmentioning
confidence: 99%
“…The objective is to reach an agreement in which life support techniques/treatments are adapted to the situation of each patient [4]. The goals of care will thus change to ensure comfort rather than to provide a cure, and families must be made to understand that the best care for their child is being provided [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we found that although the child's death required many professional tasks from the nurses, they primarily responded to the death on a personal, rather than professional, level. During the moments surrounding the death, many nurses reported feeling intense sadness and distress, which were often suppressed due to a sense that expressing such emotion would be detrimental to the family and would be perceived as “unprofessional.” However, past studies have shown that bereaved families do not view staff emotional expression as unprofessional, but rather as demonstrating compassion and caring (Brooten et al., ; Butler, Hall, Willetts, & Copnell, ; Butler et al., ; Heller & Solomon, ). We suggest that nursing staff caring for a dying child be encouraged and supported to demonstrate their emotions as appropriate with a grieving family, particularly if a strong bond has been formed with them.…”
Section: Discussionmentioning
confidence: 99%
“…Critical care environments, such as emergency departments and intensive care units, are designed to provide specialist lifesaving care to critically ill infants and children. Often, the focus is on preservation of life with highly technical therapies and precise medication management, with only limited focus on end‐of‐life care (Butler, Hall, Willetts, & Copnell, ; Copnell, ; Danis et al., ). The majority of end‐of‐life care is provided to these children and their families by highly trained, specialist nurses, who primarily remain at the bedside as a component of their professional role (Akpinar, Senses, & Aydin Er, ; Bloomer, Endacott, Copnell, & O'Connor, ; Foglia, Grassley, & Zeigler, ).…”
Section: Introductionmentioning
confidence: 99%